An Epidemiological Burns Autopsy Study Along with its Source and Severity in a Tertiary Care Hospital (Indian Internet Journal of Forensic Medicine and Toxicology, 2023)
Burns have always been considered as one of the most destructive injuries, causing not only deaths but also major economic and psychological impacts. This study has been taken up to characterize the epidemiology and to know the trend of the changing profile of the burn deaths. Materials and Methods: A total of 50 cases of death due to fatal burn injuries, which were brought to the mortuary of BPS GMCW, Khanpur Kalan, Sonipat, Haryana, India, between January 2013 and December 2015, were taken up for the study. Results: In the present, study of young women in age category of 21–30 years living in rural areas was commonly involved. Maximum number of victims were married and were housewives. Flames were most common physical agent for burn injuries in 74% of cases, whereas electrical injuries were seen in 26% cases. Maximum number of cases occurred during night-time (46%) especially around 7–8 PM or early morning. Most common manner of deaths was accident.
Keywords: Burns; Epidemiology; Injuries; Flames; Electrical; Autopsy